1927 Mich. Pub. Acts 888-89 - (:unkn) unknown (My University, 1927)
No. 372, § 3: Prohibited manufacturing, selling, or possessing a machine gun, silencer, bomb, bombshell, blackjack, slungshot, billy, metallic knuckles, sandclub, bludgeon. Punishable by fine up to $1,000 or imprisonment.
Keywords: MACHINE GUN RESTRICTION; TRANSFER, MANUFACTURE & POSSESSION